2021
DOI: 10.1002/adem.202101068
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Reduced Graphene Oxide/Elastomer Resin Composite with Structural Modulated Sensitivity for Flexible Strain Sensor

Abstract: High-performance flexible strain sensors with cost-effective and scalable fabrication methods are highly demanded for human-machine interfaces, soft robotics, and health monitoring. Herein, a digital light processing-based 3D printing method, which manufactures structures in a scalable and efficient layerby-layer manner, is developed to prepare a type of flexible strain sensors consisting of reduced graphene oxide/elastomer resin (RGO/ER) composite as the strain sensing element and RGO/ER composite with rhombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
3
21
3
Order By: Relevance
“…The data are slightly lower than those obtained for DLP 3D printed acrylic resins filled with 0.3–0.6 wt.% carbon nanotubes (10 −4 –10 −5 S cm −1 ) [ 80 , 81 , 82 ] and similar contents of PANI-HCl (10 −5 S cm −1 ) [ 31 ] or a mixture of PANI/MWCNT (10 −4 S cm −1 ) [ 32 ]. Simultaneously, the conductivity values achieved are similar or higher than those reported for printable photocurable resins using 16 wt.% (10 −6 S cm −1 ) [ 83 ] and 1 wt.% (10 −11 S cm −1 ) [ 84 ] of Ag nanoparticles or 2 wt.% reduced graphene oxide (rGO) (10 −7 S cm −1 ) [ 85 ]. By contrast, some authors have reported conductivity values of the order of 10 −2 –10 −3 S cm −1 with 6 wt.% of rGO [ 86 ] or using 20 wt.% of PEDOT [ 60 ].…”
Section: Resultssupporting
confidence: 65%
“…The data are slightly lower than those obtained for DLP 3D printed acrylic resins filled with 0.3–0.6 wt.% carbon nanotubes (10 −4 –10 −5 S cm −1 ) [ 80 , 81 , 82 ] and similar contents of PANI-HCl (10 −5 S cm −1 ) [ 31 ] or a mixture of PANI/MWCNT (10 −4 S cm −1 ) [ 32 ]. Simultaneously, the conductivity values achieved are similar or higher than those reported for printable photocurable resins using 16 wt.% (10 −6 S cm −1 ) [ 83 ] and 1 wt.% (10 −11 S cm −1 ) [ 84 ] of Ag nanoparticles or 2 wt.% reduced graphene oxide (rGO) (10 −7 S cm −1 ) [ 85 ]. By contrast, some authors have reported conductivity values of the order of 10 −2 –10 −3 S cm −1 with 6 wt.% of rGO [ 86 ] or using 20 wt.% of PEDOT [ 60 ].…”
Section: Resultssupporting
confidence: 65%
“…The conductivity values achieved are higher than those reported for printable photocurable resins using other fillers such as nanoparticles of Ag (10 −6 –10 −11 S cm −1 ) [ 59,60 ] or reduced graphene oxide (rGO) (10 −7 S cm −1 ). [ 61 ] By contrast, some authors have reported higher conductivity [ 62 ] values in the order of 10 −2 –10 −3 S cm −1 , although using a much higher amount of fillers such as 6% of rGO [ 63 ] or 20% of PEDOT. [ 55 ] The use of high amounts of filler is not desirable considering their cost and the negative effect on the performance of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the cost-effectiveness of screen printing makes the use of large area electronic or tactile skin in robotics possible. 122 While AJP 35,45,67,123 and DLP 38,40,42,43,124,125 have been applied for the fabrication of flexible mechanical sensors, they are less common due to various reasons. For example, although AJP is a newly developed printing technique with high resolution 91 and fast printing speed, 90 the cost of AJP is much higher in contrast to other techniques; while DLP can fabricate sophisticated 3D geometries with high resolution and rapid speed, the requirement of a photocurable resin limits the material selection.…”
Section: Changhong Caomentioning
confidence: 99%
“…2.1.3 Graphene-based. All graphene-based flexible strain sensors identified in the literature have a relatively large sensing range, 124,[136][137][138] as shown in Fig. 2.…”
Section: Cnt-basedmentioning
confidence: 99%
See 1 more Smart Citation